Innovation in Architecture: The Role of Digital Technologies and Social Networks in Academic Education - Pérez Nanclares, Carlos Mario; Del Blanco García, Federico Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research analyzes the role of certain social networks as educational tools in learning architecture, specifically in project workshops focused on parametric design, a method closely linked to the conceptualization and application of computational design. The research focuses on the question of whether these digital experiences can match social interaction in design workshops, an aspect considered essential by several education experts for the development of technical and creative skills.